SUBJECTIVE ASSESSMENT OF CHANGES IN LIFE DURING COVID-19 PANDEMIC: COMPARISON OF POLISH AND UKRAINIAN ADULTS - Ewa Małgorzata Szepietowska; Ewa Zawadzka; Sara Filipiak (Психологічні перспективи, 2022)
Purpose. The first stage of the COVID-19 pandemic was associated with the growing sense of massive trauma and loss. The current research suggests that the past two years of the pandemic are perceived in terms of both losses and gains. The study aimed to compare opinions expressed by adult Poles and Ukrainians, about changes in various spheres of life resulting from the two years of the pandemic.